2020
DOI: 10.1080/00380768.2020.1864230
|View full text |Cite
|
Sign up to set email alerts
|

Limited effects of the soluble organic phosphorus fraction on the root phosphorus uptake efficiency of upland rice genotypes grown in acid soil

Abstract: The root phosphorus (P) uptake efficiency (RE), defined as plant P uptake per unit root mass or root area, may contribute to the P efficiency of upland rice grown in acid, P-deficient soils. The identification of root traits conferring RE of rice has been compromised by the lack of attention given to P speciation when evaluating P-mining mechanisms. Here we disentangled the effect of soluble organic P (PO) from that of total soluble P (PT) on the RE in rice seedlings in acid soil. Six rice genotypes were grown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Wissuwa and Ae (2001) investigated the P uptake of 30 rice genotypes and observed a high variation for P uptake (0.6–12.9 mg P per plant). Several recent studies in rice and other crops have reported that using genotypes with high P‐uptake efficiency is the best approach for P‐deficient soils, while genotypes with P efficiency produce sufficient dry matter per unit of P consumption (Bilal et al, 2018; Iqbal et al, 2019; Sandaña, 2016; Shimamura et al, 2020). Typically, low P (LP) limits the aboveground growth of rice (i.e., number of tillers, shoot biomass, leaf area index (LAI), and leaf photosynthetic rate), and varieties with strong tolerance to LP could adapt to LP environment by increasing the root growth (Deng et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Wissuwa and Ae (2001) investigated the P uptake of 30 rice genotypes and observed a high variation for P uptake (0.6–12.9 mg P per plant). Several recent studies in rice and other crops have reported that using genotypes with high P‐uptake efficiency is the best approach for P‐deficient soils, while genotypes with P efficiency produce sufficient dry matter per unit of P consumption (Bilal et al, 2018; Iqbal et al, 2019; Sandaña, 2016; Shimamura et al, 2020). Typically, low P (LP) limits the aboveground growth of rice (i.e., number of tillers, shoot biomass, leaf area index (LAI), and leaf photosynthetic rate), and varieties with strong tolerance to LP could adapt to LP environment by increasing the root growth (Deng et al, 2020).…”
Section: Introductionmentioning
confidence: 99%